2007
DOI: 10.1136/vr.161.11.371
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of cleaning and disinfection on pig farms in Ireland

Abstract: Little is known about the effectiveness of the cleaning and disinfection methods used on commercial pig farms either in Ireland or worldwide. A National Salmonella Control Programme was implemented in Ireland in August 2002 to monitor and control the infection of pigs with Salmonella species. Commercial pig herds must be categorised according to their Salmonella status as either category 1, 2 or 3, having a serological prevalence of infection with Salmonella serotypes up to 10 per cent, between 10 and 50 per c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 26 publications
(4 reference statements)
2
58
1
1
Order By: Relevance
“…A recent study conducted in pig barns showed that the cleaning and disinfection protocol used effectively reduced the level of Salmonella; however, there was not complete elimination of Salmonella using cleaning and disinfection procedures in the barns. This finding suggests that there is a need for multiple intervention procedures at different stages or perhaps more stringent disinfection protocols in swine production environments (18). An in vitro trial in our laboratory showed that some strains of Salmonella may develop tolerance to biocides, including commonly used disinfectants (unpublished data).…”
Section: Discussionmentioning
confidence: 98%
“…A recent study conducted in pig barns showed that the cleaning and disinfection protocol used effectively reduced the level of Salmonella; however, there was not complete elimination of Salmonella using cleaning and disinfection procedures in the barns. This finding suggests that there is a need for multiple intervention procedures at different stages or perhaps more stringent disinfection protocols in swine production environments (18). An in vitro trial in our laboratory showed that some strains of Salmonella may develop tolerance to biocides, including commonly used disinfectants (unpublished data).…”
Section: Discussionmentioning
confidence: 98%
“…Typically they employ yeast either as whole killed cells or an extract and/or serum albumin to simulate dirty conditions. The limitations of C&D in Salmonella-contaminated layer and pig units have been documented (Wales et al, 2006(Wales et al, , 2009Mannion et al, 2007), and in the authors' experience some disinfectants with proven performance in the standard tests do not appear to be as efficacious in field situations. There are many possible reasons for the failure of a disinfectant to perform as desired in a farm environment, and these include: unsuitable dilutions or coverage rates being used, inadequate prior cleaning (Ward et al, 2005(Ward et al, , 2006, and difficulties with access particularly in accommodation with complex equipment such as layer hen houses.…”
Section: Introductionmentioning
confidence: 93%
“…The pathogen is common, persists in the environment, and infections with most serovars occur without any obvious symptoms (Davies et al, 2004;EFSA, 2008). Although hygiene and biosecurity on-farm are of paramount importance in decreasing Salmonella seroprevalence in slaughterhouses (Hotes et al, 2011), Salmonella-free housing cannot be obtained simply by cleaning and disinfection regimens at farm level (Mannion et al, 2007;McLaren et al, 2011). Hence, such regimens should be combined with other measures as part of an overall strategy to control Salmonella on-farm (Wales et al, 2009).…”
Section: Introductionmentioning
confidence: 99%